Assessing medical student performance of Entrustable Professional Activities: A mixed methods comparison of Co-Activity and Supervisory Scales. (3rd March 2020) - Cutrer, William B.; Russell, Regina G.; Davidson, Mario; Lomis, Kimberly D.
Abstract: Introduction: Observations of medical student participation in entrustable professional activities (EPAs) provide insight into the student's ability to synthesize competencies across domains and effectively function in different clinical scenarios. Both Supervisory and Co-Activity Assessment Scales have been recommended for use with medical students. Methods: Students were assessed on EPAs during Acting Internships in Medicine and Pediatrics. Two rating scales were modified based on expert review and included throughout the 2017–18 academic year. Statistical analysis was conducted to clarify relationships between the scales. Raters were interviewed to explore their interpretations and response processes. Results: The results of the McNemar test suggest that the scales are different ( p -value <.01). Co-activity and Supervisory EPA ratings are related, but not interchangeable. This finding concurs with themes that emerged from response process interviews: (1) the scales are not directly parallel (2) rater preference depends on diverse factors and (3) rater comments are crucial for guiding students' future learning. Conclusion: The modified Chen Supervisory Scale and the modified Ottawa Co-Activity Scales are measuring different aspects of the entrustable professional activity landscape. Both scales can provide useful information to the learner and the assessment system, but they should not be treated as interchangeable assessments.